The Influence of Market Orientation, Entrepreneurial Orientation and Innovation on The Performance of Micro, Small and Medium Enterprises (Msmes) In Harapan Baru Sub-District - Rahma, Novia Hanifah; Rianto, Muhammad Richo; Woestho, Choiroel (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
English This research was conducted to determine the partial or simultaneous influence of the independent variables, namely Market Orientation, Entrepreneurship Orientation and Innovation on the dependent variable, namely MSME Performance. This research uses quantitative methods. The population in this research is MSME business actors in Harapan Baru Village, North Bekasi District, Bekasi City. The number of samples used in this research was 55 respondents. Data collection techniques use questionnaires and data processing and hypothesis testing using Smart-PLS 4.0. The results of this research explain that the Market Orientation variable has no and no significant effect on MSME Performance, the Entrepreneurial Orientation variable has a positive and significant effect on MSME Performance and Innovation has a positive and significant effect on MSME Performance.